A study on Islamic bank’s performance: a case of Bank Kerjasama Rakyat Malaysia for five years (2004 - 2008) / Roszalina Zainol - Zainol, Roszalina (2009)
The study evaluates the Islamic bank’s performance of Bank Kerjasama Rakyat in profitability, liquidity and risk and solvency for the period 2004- 2008.Financial ratios are applied in measuring these performances and f-test are used in determining their significance. The objective of the study is to measure and analyze the performance level of Bank Rakyat as local Islamic bank in Malaysia compared to conventional banks (United Overseas Bank Malaysia) in profitability, liquidity also risk and solvency. The specific objectives of the study are to evaluate the performance of Islamic Bank and to see whether there is a significant different in performance between Islamic bank and conventional bank. Study made by (Abdus Samad & Hassan, 1999), the profitability performance of Islamic bank in Malaysia (BIMB) was compared to 8 conventional banks using the financial ratios. The study found that the average profit of BIMB is significantly lower than the conventional banks. This paper found the Bank Kerjasama Rakyat Malaysia is less profitability compared to United Overseas Bank, but more liquid, less risky and more solvent compared to United Overseas Bank. Bank Kerjasama Rakyat Malaysia should make an effort to focus on increasing the market share in credit card, personal financing and other products increase profitability.